Pendidikan Kewarganegaraan paradigma baru dan implementasinya dalam kurikulum berbasis kompetensi - Muchson AR (Jurnal Civics: Media Kajian Kewarganegaraan, 2004)
Up to now, Civic Education was utilized as an instrument for regime (to support them). The common perception, this subject was more political in favor than academic one. With the spirit of reformation, new paradigm of Civic Education should be self-reformed, include reorientation both vision and mission. Revitalization of role, and structuring curriculum. In the new Indonesia Civic Education discourse, the comprehensive compentencies of Civic Education include civic knowledge, disposition, and skill.